Medical Ecology in The System of Reducing General Disease: Study of Features of Photosynthetic Activity of Mosses on Posttechnogenic Technics - Baik Оксана; Kyyak Наталія; Humeniuk Ольга (Actual Problems of Medicine and Pharmacy, 2021)
It is shown that bryophytes are characterized by a high content of photosynthetic pigments and the intensity of photosynthesis. The activity of photosynthetic processes of mosses depends on species characteristics and habitat. For all studied species of mosses, a direct correlation was established between the intensity of photosynthesis and the content of chlorophylls in the leaves of mosses. Analysis of the daily dynamics of moss photosynthesis demonstrated the adaptability of the moss photosynthetic apparatus to contrasting climatic conditions in the dump area and the ability to maintain the intensity of photosynthesis processes at a fairly stable level during the growing season. For the first time, the productivity of moss cover in the dump area оце1 was estimated, which indicates the important role of bryophytes in the production process in man-made areas of sulfur production. The system of public administration in the field of water protection requires immediate reform and the transition to integrated water resources management on a basin basis. Establishment of maximum permissible concentrations of chemicals in the form of nanoparticles, the problem of low-intensity toxicity, the study of mechanisms and manifestations of cardiovasotoxic effects of exogenous chemical stimuli of industrial and environmental conditions is extremely important. The establishment of a regional program of integrated multidisciplinary research will help to study the causes and conditions of contributing to water pollution, leading to various diseases of the population, reducing the body's overall resistance and, consequently, increasing overall morbidity, including infectious and cancer diseases.